(untitled) (ARQUISUR Revista, 2011)
The investigation focuses on a set of works that have been neither performed by architects, nor possess academic legitimization. The hypothesis: the presence of coffeehouses and bars in the European culture moved to Montevideo as an expression of a correlation detecting constant elements in the constitutive guidelines and in formal and sensitive categories. Those invariants induce the recognition of the archetypical elements which make up the essence of the architectural program, in close connection with a certain model of the city and putting a stamp on urban identity. The method based itself in the tool chosen for study cases: the drawing as a way of thinking architecture. The conclusions analyze the role that coffeehouses and bars played within the city, acting as engines within the set of rules of an unplanned urbanism. Nowadays, the city is no longer articulated by them. Inexorably, the megastructures (shopping centres and hypermarkets) have entered into scene, multiplying, "sucking in" every competitor. They are the consequences of junkspace –a term coined by Koolhaas–, imposing conceptual changes in architecture through the application of a unique model, one which is globalizing, and determines that all cities end up looking alike.